Utilizing the renal and vertebral contours as landmarks for right adrenal vein localization in primary aldosteronism: a retrospective analysis of 310 cases - Sha, Wei; Du, Yun; Rong, Shunkang; Yao, Yuanqing; Xiong, Bo; Liu, Han; Qian, Jun (Frontiers in Endocrinology, 2025)
BackgroundAdrenal Vein Sampling (AVS) is the gold standard for categorizing primary aldosteronism (PA). However, catheterization of the right adrenal vein (RAV) can be technically challenging. This study aimed to investigate the validity of the right renal vertebral contour as fluoroscopic landmarks to help RAV orifice localization during AVS.MethodsImaging data of 310 PA patients were retrospectively analyzed. Patients were divided into Normal, Overweight, and Obese group based on their body mass index (BMI). A novel Renal-Vertebral-Angle (R-V-A) model was employed to delineate the distribution of the RAV orifice. This model concerned a cruciate cross formed by the upper edge of the right renal and the right edge of vertebral contour under fluoroscopy. The area within a 2 cm×2 cm square in the left upper quadrant of this cross was defined as the R-V-A. The success rate of AVS was compared across different BMI groups, as well as the differences in the distribution of the RAV orifice within the R-V-A.ResultsSuccessful RAV sampling was achieved in 270 cases, while the success rate of RAV sampling was found to be lower in the Obese group. The majority of the RAV orifices were located within the R-V-A region (249/270, 92.2%). There was no significant difference in the distribution of RAV orifices across the BMI groups (Normal vs. Overweight vs. Obese: 92.2% vs. 91.9% vs. 93.3%, p=0.968). In contrast to patients with successful RAV sampling, a significantly lower proportion of sampling site were found within the R-V-A in cases with mis-catheterized cases (92.2% vs. 55.6%, p<0.001).ConclusionThe R-V-A model could be utilized as an anatomical landmark for the RAV orifice localization on fluoroscopy, that might help to narrow down the exploration range for RAV catheterization, and might offer beneficial assistance in enhancing the success rate for AVS.